2015
DOI: 10.1186/s13568-015-0110-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cake compositions, pepsin digestibility and amino acids concentration of proteins isolated from black mustard and yellow mustard cakes

Abstract: As a byproduct of oil production, black and yellow mustard cakes protein are considered as potential source of plant protein for feed applications to poultry, fish and swine industries. The protein contents in black and yellow mustard cakes were 38.17% and 28.80% and their pepsin digestibility was 80.33% and 77.43%, respectively. The proteins were extracted at different pH and maximum proteins (89.13% of 38.17% and 87.76% of 28.80% respectively) isolated from black and yellow mustard cakes at pH 12. The purity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
13
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 17 publications
10
13
4
Order By: Relevance
“…Significantly highest amount of nitrogen content was obtained from BARI Sarisha-15 (4.48%), the lowest amount of nitrogen content found in BARI Sarisha-17 (3.67%) ( Table-6). The present studies values are more or less similar with the reported values of Sarker et al, (2015), Sosulki et al, (1991), Chowdhury et al, (2010), and Mirza et al (1998).…”
Section: Proximate Analysis Of Minerals Content Of the Different Oilssupporting
confidence: 93%
See 4 more Smart Citations
“…Significantly highest amount of nitrogen content was obtained from BARI Sarisha-15 (4.48%), the lowest amount of nitrogen content found in BARI Sarisha-17 (3.67%) ( Table-6). The present studies values are more or less similar with the reported values of Sarker et al, (2015), Sosulki et al, (1991), Chowdhury et al, (2010), and Mirza et al (1998).…”
Section: Proximate Analysis Of Minerals Content Of the Different Oilssupporting
confidence: 93%
“…Magnesium content of different varieties was ranged from 0.64% to 0.740%. The present investigations were supported by reported value of Sarker et al, (2015), Sengupta et al, (2003), Chowdhury et al,(2015), Bachheti et al, (2012), Josefson (1988), and Pathak et al, (1973).…”
Section: Proximate Analysis Of Minerals Content Of the Different Oilssupporting
confidence: 89%
See 3 more Smart Citations